Pengaruh Profitabilitas dan Likuiditas Terhadap Pengungkapan Sustainability Report di Perusahaan Yang Terdaftar Pada Jakarta Islamic Index (JII) - Marsuking Marsuking (JESI (Jurnal Ekonomi Syariah Indonesia), 2020)
This study aims to examine the effect of profitability and liquidity on the disclosure of sustainability reports. The independent variables in this study are profitability and liquidity. While the dependent variable is the sustainability report disclosure. The population of this research is companies listed on the Jakarta Islamic Index (JII) in 2016-2018. The research sample was taken using purposive sampling method. Based on the purposive sampling method, the number of companies that have disclosed their sustainability reports is 42 companies. The analysis method used in this study is multiple regression analysis, classic assumption test, determination coefficient test, and hypothesis testing conducted with SPSS 20. The results of this study indicate that profitability and liquidity do not affect the disclosure of sustainability reports.